ANALYSIS OF LANDSLIDES RISK IN DANO VILLAGE LELES DISTRICT GARUT REGENCY WEST JAVA - Fachry Arsyad; Dede Kuswanda; Milly Mildawati (Indonesian Journal of Social Work, 2020)
The study aims to obtain the overview of landslide risk in Dano Village, Leles District, Garut Regency. Disaster risk is the potential for losses arising from disasters. Level of disaster risk is the result of multiplication between threat and vulnerability divided by capability, meaning that the greater the threat and vulnerability while the smaller the capability, the greater the risk of disaster. The research method used a descriptive survey research methods with quantitative approaches. The research respondents were administrators and members of the Disaster Preparedness Village and Chairman of RW 06, 07 and 08 Kampung Patrol in total 46 respondents. Data collection techniques using a questionnaire. The results showed that in Dano Village, Leles Subdistrict, Garut Regency, there was a high category of landslide threat, a high category of vulnerability to landslides, and a low category of capability to encounter disaster threats. In general, Dano Village has a low level of disaster risk. Recommended research results are: a necessary effort to reduce the risk of landslides by depressing the threat of landslides, decreasing vulnerability to landslides, and increasing the capability on facing landslides. The next research recommendation is to examine the variable of preparedness to encounter the threat of landslides.